P4-S1.06 High-resolution Multilocus Sequence Typing (MLST) of Chlamydia trachomatis from three catchment areas in North and Central Norway. (10th July 2011) - Herrmann, B; Christerson, L; Gravningen, K; Stahlsten, A; Ödman, K; Nguyen, D; Isaksson, J; Furberg, A S; Simonsen, G S
Abstract : Background: The C trachomatis incidence rate in the county of Finnmark in North Norway is twice as high as in the rest of the country. This study genetically characterises the C trachomatis strains in Finnmark and compares them with strains from two other counties in Norway. Methods: DNA sequencing of ompA, which encodes the major outer membrane protein MOMP, and a high-resolution multilocus sequence typing (MLST) system, which is based on PCR amplification and DNA sequencing of five highly variable genetic regions (not housekeeping genes as in conventional MLST), were used. In total, 80 specimens from adolescents mainly aged 15–19 were collected in five high schools (n=60) and in the laboratory routine (n=20) in Finnmark (extended county with sparse population in minor municipalities) and compared to 80 laboratory specimens from Tromsø county (capital of North Norway) and 88 laboratory specimens from Trondheim in Central Norway. Results: Sequencing of ompA detected 11 genotypes in these 248 specimens. The MLST analysis displayed 50 sequence types (STs), providing five times higher resolution than ompA. Thirty-one (62%) of the STs were novel. The study revealed overlapping STs between the different counties, but 64% of the STs were unique for specific counties (Abstract P4-S1.06 figure 1 ). The MLST genetic diversity was lower in Finnmark (0.26 ST per specimen compared to 0.34 in Tromsø and 0.32 in Trondheim, respectively), but the geographical differences were not statistically significant.The common ompA genovar E predominated in Tromsø and Trondheim (55%) whereas genovar G (36%) was most frequent in Finnmark. Conclusions: Our MLST provided a significantly higher differentiation capacity than conventional ompA typing, which has predominated genotyping of C trachomatis for decades. Thus high-resolution MLST is a useful tool for molecular epidemiology of chlamydial infections.